Characteristic of concrete using acetylene sludge as a substitute material for sand and cement - Dwi Indrawati; Rian Prasetyo Wisnu; Hilarion Widyatmoko (Graduate Program of Syiah Kuala University, 2017)
Acetylene sludge comes from the production of acetylene gas which is produced in large quantities from industrial plants. Since acetylene sludge waste has a baling and mortar properties as well as lime derivative products, they can be used as substitutes or substitutes for cement in concrete products and other construction materials. The aim of this study is to obtain a concrete with a proper strength and comply the toxicity standards by utilizing acetylene sludge waste. The waste (containing of 60% acetylene sludge and 40% fly ash) is utilized by mixing it on some series of trial that are 5%, 10%, and 15% waste from the main concrete materials. The concrete strength is measured using Compressive Strength Test Method that refers to Indonesian National Standard No. 1974:2011. Other than that, Toxicity Characteristic Leaching Procedure (TCLP) test were also done using Optical Emission Spectrometer to determine the leaching potential from concrete utilization. The concrete paste gave the value of slump 6 and 7 with concrete mixture declined by 15-18 cm. Result showed that the strongest concrete is from the mixture of 15% sand material that was substituted by the acetylene sludge waste with the strength value of 41.9 MPa. TCLP test results were given the value of Barium 0.019 mg/L and Chromium 0.680 mg/L with a pH value of 12.24. Referring to Indonesian Government Regulation No. 101 Year 2014, the quality standards of Barium and Chromium are 35 mg/L and 2.5 mg/L. That showed the characteristic of concrete which is produced from acetylene sludge waste complies the standards and safe for the environment.